Effectiveness of self-instructional module on knowledge regarding emotional intelligence among nursing undergraduates - Dixit, Priyanshi; Tiwari, Surya Kant; Kumar, Pankaj; Sepat, Sushila; Bugalia, Uttam (International Journal Of Community Medicine And Public Health, 2023)
Background: Nursing profession requires not only technical expertise but also holistic care, including emotional and social aspects. Nursing student must effectively manage their emotions in stressful situations. This study aimed to assess the effectiveness of the self-instructional module in enhancing knowledge regarding emotional intelligence among nursing undergraduates. Methods: A pre-experimental one-group pre-test post-test design was utilized to collect data from 100 nursing students by using a non-probability convenient sampling technique. After the pre-test, a self-instructional module was administered over two sessions, with daily one-hour for three days. The post-test was administered seven days after the intervention. Results: A significant mean difference was observed between the mean pre-test knowledge scores and the mean post-test knowledge scores. (10.81±2.82 vs 21.22±2.74, p<0.001) The study also revealed that socio-demographic parameters like gender, residence, monthly family income, and extracurricular activities influenced pre-test knowledge scores. Conclusions: The self-instructional module effectively improved emotional intelligence among nursing students, enhancing their understanding of this crucial aspect.